Rechtsanwälte und politische Prozesse in der späten DDR: eine quantitative Auswertung von MfS-ermittelten Prozessen 1984 = Lawyers and political trials in the late GDR: a quantitative analysis of cases investigated by the Stasi (MfS - Ministry of State Security) in 1984 - Booß, Christian (2012)
"By applying statistics to the records about political trials in 1984 found in the archives of the Stasi the author tries to find out how those trials where manipulated and with what strategies the lawyers defended their clients. The basis for this analysis were about 700 cases, in which the Ministry of State Security or its Berlin branch were pre-investigating for the prosecution as an 'investigating body' according to the code of criminal procedure. Through statistical analysis factors were determined that influenced the process of trial and sentencing. Of particular interest was the question of whether parties to the proceedings were controlled directly or indirectly by the state power. The main focus of the research was directed at the lawyers: How much leeway did they have and how much use did they make of it? Did those lawyers who were unofficial collaborators (IM) of the Stasi behave differently? Did a prospective release from citizenship of East Germany, i.e. the promise to